HUBUNGAN POLA MAKAN DENGAN PENINGKATAN KADAR KOLESTEROL LANSIA DI DESA TENGGELA KECAMATAN TILANGO - Hamna Vonny Lasanuddin; Rosmin Ilham; Rianti P. Umani (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2022)
Aging is a process that occurs continuously and causes several changes in the body that will affect functions that can increase cholesterol levels in the body. This research aims to determine whether there is a relationship between diet and cholesterol levels in the elderly in Tenggela Village, Tilango District. The research design used an analytic survey method with a cross sectional approach. The sampling technique used was purposive sampling. The sample was the elderly who lived in the village of Tenggela. Methods of data collection used a questionnaire. The results of the Chi-Square analysis test obtained a p value of 0.000 which is smaller than a value of 0.05, which means that H0 is rejected and Ha is accepted or there is a relationship between diet and the incidence of cholesterol in the elderly in Tenggela Village, Tilango District. Suggestions for the village government It is necessary to improve education in the form of socialization for the elderly or families about how to prevent hypercholesterolemia in the elderly